A post-occupancy evaluation on indoor environment and its significance on learning performance for higher learning education building / Pangiran Shafiq Pangiran Julaini - Pangiran Julaini, Pangiran Shafiq (2022)
Malaysia's tropical climate is hot and humid. This situation could have an adverse impact on the comfort of occupants in any place. It is reported that in 2018, all schools in Kedah and Perlis were to be closed from teaching and learning for two days due to extremely hot and dry weather caused by the El Nino Phenomenon. Meanwhile, in Malaysia, there is research that found that the occupant was not satisfied with the number of occupants inside of a building which had become too crowded. The research aim is to develop an assessment tool of Post Occupancy Evaluation (POE) for institutes of higher education building in Malaysia. The objectives of this research are to identify occupant satisfaction towards an indoor environment in the classroom and to analyze the relationship between the indoor environment and their learning performance. This research also will develop a Post Occupancy Evaluation (POE) framework that incorporates indoor environment and learning performance. A field experiment by using sets of questionnaires was conducted at three colleges in Perlis to study the objectives. Apart from frequency and descriptive analysis, correlation and multiple regression analysis was used to analyze the data. The result found that the occupant satisfaction towards the indoor environment in the classroom is at the average level while the relationship between indoor environment and learning performance is at the average level.